An Autonomous Soft Actuator with Light‐Driven Self‐Sustained Wavelike Oscillation for Phototactic Self‐Locomotion and Power Generation. (7th February 2020) - Yang, Lulu; Chang, Longfei; Hu, Ying; Huang, Majing; Ji, Qixiao; Lu, Pin; Liu, Jiaqin; Chen, Wei; Wu, Yucheng
Abstract: Mimicking the intelligence of biological organisms in artificial systems to design smart actuators that act autonomously in response to constant environmental stimuli is crucial to the construction of intelligent biomimetic robots and devices, but remains a great challenge. Here, a light‐driven autonomous carbon‐nanotube‐based bimorph actuator is developed through an elaborate structural design. This curled droplet‐shaped actuator can be simply driven by constant white light irradiation, self‐propelled by a light‐mechanical negative feedback loop created by light‐driven actuation, time delay in the photothermal response along the actuator, and good elasticity from the curled structure, performing a continuously self‐oscillating motion in a wavelike fashion, which mimics the human sit‐up motion. Moreover, this autonomous self‐oscillating motion can be further tuned by controlling the intensity and direction of the incident light. The autonomous actuator with continuous wavelike oscillating motion shows immense potential in light‐driven biomimetic soft robots and optical‐energy‐harvesting devices. Furthermore, a self‐locomotive artificial snake with phototaxis is constructed, which autonomously and continuously crawls toward the light source in a wave‐propagating manner under constant light irradiation. This snake can be placed on a substrate made of triboelectric materials to realize continuous electric output when exposed to constant light illumination. Abstract : A curled droplet‐shaped carbon‐nanotube‐based autonomous actuator is designed, producing a continuous self‐oscillating motion in a wavelike fashion under constant light irradiation, similar to the sit‐up motion. This actuator can autonomously and continuously crawl toward the light source in a wave‐propagating manner, showing phototactic self‐locomotion. Moreover, after being placed on a triboelectric substrate, it generates continuous electric output under constant light irradiation.